Pengembangan nilai-nilai karakter dalam aktivitas belajar menggunakan media pembelajaran “Pecango“ - Martina Lona Jusita (Universitas Negeri Malang, 2016)
In learning of Social Sciences (IPS) character education can be integrated in the process of learning activities associated with the context of everyday life. Understanding of the material relics of history patterned kingdom of Hindu and Buddha too difficult if you rely on the transfer of knowledge from teacher to student. Impressed learning Social Science (IPS) at junior level that causes less optimal learning process becomes drab as well boring. In addition, cultivation of character values do not appear in the learning process. Thus the need to develop character values in learning activities by using certain learning media. Given Malang has a legacy of temples patterned Hindu-Buddhist saves philosophies sublime related to the values of the characters inscribed on the panels, then compiled instructional media